2020
DOI: 10.1002/pbc.28778
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of central giant cell granuloma in children with denosumab

Abstract: Central giant cell granuloma (CGCG) is a benign but locally aggressive intraosseous lesion of the mandible. Historically, it is treated by curettage or resection. Medical therapy is indicated when surgery is associated with increased morbidity or in adjuvant setting to decrease recurrence. Treatment of CGCG with denosumab, a receptor activator of nuclear factor kappa‐beta (RANK) ligand inhibitor, is not well studied, especially in children. Here, we describe our experience with the use of denosumab in the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
2
12
0
5
Order By: Relevance
“…More recently, Choe et al reported six children (age range: 5–12 years) presenting aggressive CGCG lesions, who were successfully treated with subcutaneous denosumab. Interestingly, three patients developed hypocalcemia during denosumab course, and three patients developed rebound hypercalcemia associated with kidney injury 5 months after treatment 17 . The exact same pattern was observed in four patients with Noonan syndrome, 18 and one patient with cherubism 19 treated with denosumab.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…More recently, Choe et al reported six children (age range: 5–12 years) presenting aggressive CGCG lesions, who were successfully treated with subcutaneous denosumab. Interestingly, three patients developed hypocalcemia during denosumab course, and three patients developed rebound hypercalcemia associated with kidney injury 5 months after treatment 17 . The exact same pattern was observed in four patients with Noonan syndrome, 18 and one patient with cherubism 19 treated with denosumab.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, three patients developed hypocalcemia during denosumab course, and three patients developed rebound hypercalcemia associated with kidney injury 5 months after treatment. 17 The exact same pattern was observed in four patients with Noonan syndrome, 18 and one patient with cherubism 19 treated with denosumab. Noteworthy, Naidu et al reported the development of mild hypercalcemia during denosumab treatment of CGCG in a 9-year-old girl, which led to discontinuation of denosumab; however, the authors gave little attention to this event.…”
Section: Discussionsupporting
confidence: 59%
“…Our database search revealed only 9 adult cases (Group M), contrary to 40 juvenile and adolescent cases (Group I), even though denosumab has been widely used in adult patients in the past decade. According to reports of consecutive case series of skeletally immature patients treated with denosumab, hypercalcemia occurred in 14 of 31 cases (4 of 4 cases with Noonan syndrome and CGCG [22] , 3 of 6 cases with CGCG [23] , 2 of 4 cases with osteogenesis imperfecta [24] , 2 of 9 cases with ABC [25] , 2 of 5 cases with ABC [26] , one of 3 cases (ABC, CGCG, and cherubism) [27] ), indicating that this event occurs as frequently as 45% in juvenile and adolescent patients. In contrast, phase 2 clinical study of denosumab in patients with GCTB (>12-year-old) showed that the frequency of hypercalcemia was <1% (4 of 526 cases) [28] .…”
Section: Discussionmentioning
confidence: 99%
“…However, in severe cases, repeated use of bisphosphonates or reinjection of denosumab was often required to repress the surge of calcium released into the circulation 14 , 16 , 17 , 19 , 22 , 24 , 29 , 30 , 31 , 32 , 33 , 34 . Although no established treatment modality exists to prevent this condition, tapering of the dosage of denosumab and prophylactic use of bisphosphonates were attempted in several cases 22 , 23 , 31 . However, due to the small number of cases, the clinical benefit of these methods is currently inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…O tratamento das LCCG se dá tradicionalmente por remoções cirúrgicas seguidas ou não de curetagem (Choe et al, 2021). Há também medidas suplementares, como a criocirurgia ou osteotomia periférica.…”
Section: Discussionunclassified